Poplars in India - Mathur, R. S.; Sharma, K. K. (Indian Forester, 1983)
In the context of raising large scale plaotationo of suitable quick growing species to meet the increasing demands for wood and conservation of environment,various clones of Poplars both indigenous and exotic, have assumed a special significance because of their fast rate of growth in our regulur plantation programmes. Poplars have been found eminently suitable under agro-forestry. The paper presents the results of trials with various clones of Populus species and hybrids conducted in India. Growth and yield estimates of poplars have also been described and tbe expenditure aud expected returns from tbe plantalion. Raised as pure and io combination with agriculture crops have been given. Cultivation of poplars wilh agricultural crops at 8 years rotations ensures high economic returns.